Super highway or cul de sac: the internet as a tool for learning school mathematics. - Dickson, Margaret (My University, 2014)
This research report examines the possible contribution, if any, the Internet can make in enabling mathematics learning at junior secondary school level. In particular it looks at the ways and extent that learners respond to specifically designed mathematics lessons that use the Internet. The research takes the form of a case study and considers learners’ actions with, and reflections on their use of, the tool. Within a framework of communities o f practice I identify the existence o f ‘local communities o f mathematical practice’ (LCMPs) in certain mathematics lessons that use the Internet. I suggest that learning within such LCMPs cannot be fully explained without also considering notions of mediation,provided by the tool and/or a more able other. Further issues that impact on this study are the ‘visibility’ of the mathematics within more integrated lessons and the technicalities of time when working with the Internet within a South African context.